ANALISIS IMPLEMENTASI WAJIB LAPOR TENAGA KERJA PERUSAHAAN KE DINAS TENAGA KERJA KOTA JAYAPURA - Benyamin Tanda (Universitas Cenderawasih, 2020)
This study would like to give you an idea or describe and analyze the real situation of the implementation of employment policy in the company to report on the Department of Labor Jayapura Papua province as a social phenomenon, then this type of research is descriptive qualitative research. The data analysis using inductive analysis, performed analysis step is data triangulation. The results showed that : (1) The process of communication required to report employment policies of the leadership to subordinates still experiencing barriers caused parentheses implementor in understanding and field level staff in understanding and understand the contents of the charge required to report employment policies . (2) The implementation of employment policy in the company to report on the Department of Labor has not optimally touch all the companies located in the city of Jayapura. (3) The attitude of the implementers need to be improved in supporting policy implementation report obligatory especially regarding the commitment to implement the contents of the policy implementers must report employment through enhanced calling efforts through official letter, socialization, and increased field monitoring activities of all employers. (4) the Department of Labor Jayapura yet have a standard SOP procedures and reporting procedures to report that became the basis of the implementation of employment policy. (5) Implementation of policies required to report employment in Jayapura in 3 (three) years is still not implemented to the fullest, it proved the performance of listed companies under the number 100 company from the number of companies registered with the Department of Labor as many as 367 companies. (6) support and attention of the Mayor is not optimal.